The Gothic Aesthetic and Morality in Edgar Allan’s Poe’s “The Cask of Amontillado” - Awad Ibrahim, Abdul Sattar; Samih Hamoudi, Maha (Opción, 2019)
This research paper sheds light on the Gothic aesthetic and morality in Edgar Allan Poe’s short story “The Cask of Amontillado” (1846). The aim of literature is to give delight and wisdom, which can only achieved by means of its form and content. This short story, though a Gothic one of horror, cannot be exempted from this category. It derives its elements of delight from the horror it excites in both character and reader, for horror can be a pleasurable experience for them both. Poe is very well known for his Gothic short stories such as “The Cask of Amontillado,” whose subject matter is closely related to the theme of claustrophobia which arouses the kind of horror underlying the elements of suspense, interest and curiosity on the part of the reader and is part of the aesthetic elements employed by the author. Thus, concentration in this research paper is placed on the assumption that horror in fiction can be aesthetic—a pleasurable experience that is part of the delight to be aroused by literature, and on the significant moral lessons inferred from the action of this story.